Only one fifth of young Australian adults have beliefs about medical imaging for low back pain that align with current evidence: A cross-sectional study. (December 2021) - Beales, Darren; Kent, Peter; Birkrem, Magnus B.; Man Chow, Cheuk; Li, Lap Kiu; Tan, Rui Ling Joleen; Kendell, Michelle; Straker, Leon; O'Sullivan, Peter; Smith, Anne
Abstract: Background: Patients' perceptions/expectations may be a factor behind medical imaging referral rates. Few studies have investigated the beliefs that might drive expectations of medical imaging. Objectives: This study examined whether beliefs of young Australian adults with and without impactful low back pain (LBP) concerning medical scans for LBP align with current evidence. It also investigated if these beliefs were associated with clinical factors (history of impactful LBP, history of previous medical scans, LBP-related disability and the presence of leg pain) or sociodemographic factors (sex, education, income). Design: Cross-sectional observational study. Methods: 78 participants from the Raine Study with a history of impactful LBP and 85 participants with no history of impactful LBP completed a study-specific questionnaire with five statements concerning beliefs about medical imaging for LBP. All statements were not aligned with current evidence about the use of medical imaging in LBP management. Results: Only 15–21% (n = 24–34) of the participants held beliefs that were aligned with current evidence. Participants with a university education had slightly more aligned beliefs compared to those whose highest education was completing secondary school. There was no difference in the beliefs of participants based on their history of impactful LBP, or other clinical or sociodemographic factors. Conclusion: As beliefs are likely to drive care-seeking behavior, it is notable that most participants' views about the role of medical imaging for LBP were not aligned with current evidence. Therefore, this suggests a need for community education, especially for those with lower education. Highlights: We investigated patient beliefs potentially driving expectations of medical imaging. Only 15–21% of the participants held beliefs aligned with current evidence. This may influence expectations of what information medical imaging provide. Community education on what imaging provides might be beneficial.